Pengaruh Pemberian Inhalasi Aroma Terapi Lavender terhadap Kualitas Tidur Lansia di Kelurahan Harjamukti Depok - Nurulicha Nurulicha; Yulia Herawati; Imelda Diana Marsilia (Universitas Baiturrahim, 2023)
The Elderly is a process in human life characterized by a decrease in physiological, physical, psychological, social, and cognitive functions. Most of the elderly are prone to sleep problems due to various causative factors, one of which is elderly often experience changes in sleep patterns, with around 40 to 50% of the elderly experiencing sleep disturbances. This study aimed to determine the effect of inhalation of lavender aroma therapy on sleep quality in the elderly in RW 003 Harjamukti Village, Cimanggis Depok. This type of research uses quantitative data using apseudo-experimental research design. In this study, the population was 135 respondents and the sample of this study was 34. This study used purposive sampling. The normality test was carried out and the data were analyzed by the Wilcoxon test, to see the effect of giving lavender aroma therapy inhalation on the quality of elderly sleep. Based on the results of the study, it was found that after using lavender aroma therapy there were 30 (88.23%) respondents with a total score < α (0.05) which means it has a very significant difference in value. The results of the Wilcoxon testfound that 4 respondents experienced a decrease after the intervention, 1 remained, and 29 experienced an increase after receiving the intervention. So it can be concluded that the provision of lavender aroma therapy inhalation affects the quality of sleep of the elderly in RW 003 Harjamukti Keluharan Cimanggis Depok in 2022.